PERAN KADER POSYANDU DENGAN PEMANTAUAN TUMBUH KEMBANG BAYI DI UPTD PUSKESMAS TOSORA KABUPATEN WAJO - Tetti Surianti; Rosmawaty; Ibrahim; Muhammad Tahir; Asnuddin (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
Monitoring growth and development is an activity to find early on the deviation of growth, development and mental emotional deviation. Through community participation through the Posyandu (Integrated Service Post) program, monitoring of children's growth and development is always coordinated. One of the government's efforts to reduce infant mortality is empowering posyandu cadres. Wajo. The research method used is descriptive analytic using a cross sectional design. The number of samples is 80 respondents with the sampling technique using total sampling technique. The results of this study are the Role of Posyandu Cadres identified 77 posyandu cadres (98.8%) who play a good role and 1 cadre (1.3%) who plays a bad role. Monitoring of infant growth and development identified 77 (96.3%) cadres who monitor and 3 (3.8%) cadres who do not monitor. Chi Square test results obtained = 0.000 which shows = 0.000 <0.05. The conclusion is that there is a relationship between the role of posyandu cadres and monitoring the growth and development of babies in the UPTD area of ​​the Tosora Health Center, Wajo Regency.